2015
DOI: 10.1038/srep17487
|View full text |Cite|
|
Sign up to set email alerts
|

Cross-modal and modality-specific expectancy effects between pain and disgust

Abstract: Pain sensitivity increases when a noxious stimulus is preceded by cues predicting higher intensity. However, it is unclear whether the modulation of nociception by expectancy is sensory-specific (“modality based”) or reflects the aversive-affective consequence of the upcoming event (“unpleasantness”), potentially common with other negative events. Here we compared expectancy effects for pain and disgust by using different, but equally unpleasant, nociceptive (thermal) and olfactory stimulations. Indeed both pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 61 publications
(104 reference statements)
6
29
0
Order By: Relevance
“…Research on somatic and empathic (vicarious) pain can also inform future research on socially-induced placebo (and nocebo) pain modulation. Vicarious and somatic types of pain have commonalities at the neural level [15; 49] with overlapping activations in the dorsal anterior cingulate cortex, anterior insula, and other areas. Nevertheless, these activations appear to be unspecific to pain and rather related to negative affect [16; 31].…”
Section: Potential Mechanisms Of Observationally-induced Pain Changesmentioning
confidence: 99%
“…Research on somatic and empathic (vicarious) pain can also inform future research on socially-induced placebo (and nocebo) pain modulation. Vicarious and somatic types of pain have commonalities at the neural level [15; 49] with overlapping activations in the dorsal anterior cingulate cortex, anterior insula, and other areas. Nevertheless, these activations appear to be unspecific to pain and rather related to negative affect [16; 31].…”
Section: Potential Mechanisms Of Observationally-induced Pain Changesmentioning
confidence: 99%
“…Thus, the identification of shared or independent activity patterns represents a more stringent assessment of whether two conditions recruit the same or different neuronal processes 30 31 32 33 . Using MVPA, we compared activity patterns from 19 female 7 volunteers when they were subjected to either electrical (painful (Ps)/non-painful (nPs)) or gustatory stimuli (disgusting (Ds)/non-disguting (nDs)), which were carefully matched for subjective unpleasantness 34 (self-related trials). In separate (other-related) trials, they saw a befriended confederate receiving equivalent electrical (Po/nPo) or gustatory (Do/nDo) stimuli 5 .…”
mentioning
confidence: 99%
“…The design was almost identical to the original version (Cook et al, 2013) except for the types of the morphed expressions (e.g., surprise and fear in Cook et al 2013). In our study, the reasons to morph between pain and disgust instead of other emotions were twofold: 1) these two expressions share some similarities but are still distinct enough to be decoded from each other (Kunz et al, 2013;Sharvit et al, 2015); 2) though few studies have reported naltrexone could modulate aversive stimuli (Murray et al, 2014), it is still considered that the link between disgust and the opioid system is not conclusive (Nummenmaa and Tuominen 2018). In each trial, after 1500 ms fixation, a facial expression was presented on the screen, which consisted of a morph between two original images showing pain and disgust (e.g., 50% pain and 50% disgust) for 800 ms.…”
Section: Paradigmmentioning
confidence: 76%